Association of White Matter Hyperintensities With HIV Status and Vascular Risk Factors. (6th April 2021) - Mina, Yair; Wu, Tianxia; Hsieh, Hsing-Chuan; Hammoud, Dima A.; Shah, Swati; Lau, Chuen-Yen; Ham, Lillian; Snow, Joseph; Horne, Elizabeth; Ganesan, Anuradha; Rapoport, Stanley I.; Tramont, Edmund C.; et al.
Abstract : Objective: To test the hypothesis that brain white matter hyperintensities (WMH) are more common in people living with HIV (PLWH), even in the setting of well-controlled infection, and to identify clinical measures that correlate with these abnormalities. Methods: Research brain MRI scans, acquired within longitudinal studies evaluating neurocognitive outcomes, were reviewed to determine WMH load using the Fazekas visual rating scale in PLWH with well-controlled infection (antiretroviral therapy for at least 1 year and plasma viral load <200 copies/mL) and in sociodemographically matched controls without HIV (CWOH). The primary outcome measure of this cross-sectional analysis was increased WMH load, determined by total Fazekas score ≥2. Multiple logistic regression analysis was performed to evaluate the effect of HIV serostatus on WMH load and to identify MRI, CSF, and clinical variables that associate with WMH in the PLWH group. Results: The study included 203 PLWH and 58 CWOH who completed a brain MRI scan between April 2014 and March 2019. The multiple logistic regression analysis, with age and history of tobacco use as covariates, showed that the adjusted odds ratio of the PLWH group for increased WMH load is 3.7 (95% confidence interval 1.8–7.5; p = 0.0004). For the PLWH group, increased WMH load was associated with older age, male sex, tobacco use, hypertension, and hepatitis C virus coinfection, and also with the presence of measurable tumor necrosis factor α in CSF. Conclusion: Our results suggest that HIV serostatus affects the extent of brain WMH. This effect is mainly associated with aging and modifiable comorbidities.